Technical and economic feasibility of a solar-bio-powered waste utilization and treatment system in Central America - Aguilar Álvarez, Ronald Esteban (2016)
The purpose of this study was to implement and evaluate a pilot-scale and closed-loop system that synergistically combines solar thermal collector, anaerobic digester, and constructed treatment wetland to simultaneously treat and utilize organic wastes. The system utilizes 863 kg of mixed animal and food wastes to generate 263 MJ renewable energy, produced 28 kg nitrogen and phosphorus fertilizer, and reclaimed 550 kg water per day. The net revenue considering electricity and fertilizer was $2436 annually. The payback period for the system is estimated to be 17.8 years for a relatively dilute waste stream (i.e., 2% total solids). The implemented system has successfully demonstrated a self-efficient and flexible waste utilization and treatment system. It creates a win-win solution to satisfy the energy needs of the community and address environmental concerns of organic wastes disposal in the region.